2019
DOI: 10.21608/ejbo.2019.7062.1277
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Potential of a Newly Synthesized Zinc Peroxide Nanoparticles (Zno2-Nps) to Combat Biofilm-Producing Multi-Drug Resistant Pseudomonas aeruginosa

Abstract: Introduction Multidrug-resistant (MDR) bacteria remain the greatest challenge in public health care. The numbers of infections produced by such resistant strains are increasing globally. This acquired resistance of pathogens presents a key challenge for many antimicrobial drugs (Ali et al., 2019). Such multidrug-resistant (MDR) microbes make the treatment more difficult and expensive with more side effects. Many diseases showed difficulties in their treatment after the advent of MDR bacteria

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It has many applications across a variety of industries: it is used by the rubber industry [1]; it is used in the production of plastics [2], in cosmetics and pharmacy [3]; it is an oxidant for explosives and pyrotechnic mixtures [4], and a precursor to ZnO [5,6,7,8,9,10,11,12,13,14]; it is a photocatalyst [15,16], a luminophore [17,18]; it can be used to purify water [19] and as a detoxification agent against mustard gas [20]. Recently, antibacterial and antiviral properties of ZnO 2 nanoparticles were also reported [21,22]. A progress report by Hu et al published in 2021 summarizes and discusses the advances in the construction of versatile metal peroxide nanoparticles for disease-specific chemoreactive nanotherapeutics [23].…”
Section: Introductionmentioning
confidence: 99%
“…It has many applications across a variety of industries: it is used by the rubber industry [1]; it is used in the production of plastics [2], in cosmetics and pharmacy [3]; it is an oxidant for explosives and pyrotechnic mixtures [4], and a precursor to ZnO [5,6,7,8,9,10,11,12,13,14]; it is a photocatalyst [15,16], a luminophore [17,18]; it can be used to purify water [19] and as a detoxification agent against mustard gas [20]. Recently, antibacterial and antiviral properties of ZnO 2 nanoparticles were also reported [21,22]. A progress report by Hu et al published in 2021 summarizes and discusses the advances in the construction of versatile metal peroxide nanoparticles for disease-specific chemoreactive nanotherapeutics [23].…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm formation occurs in two sequential steps by initial attachment of the bacteria to a solid surface and through the proliferation and accumulation of cells in multilayers and enclosing of the bacterial community in a polymeric matrix this matrix is essentially constituted by exopolysaccharides, but it can also contain surface proteins responsible for the bacteria attachment to surfaces (Oliveira et al, 2006), also contributing to the evasion of the immunological defenses and to the difficulty of pathogen eradication, often resulting in persistent infections (Melchior et al, 2006;El-Shouny et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…HPLC results also revealed that the rates of degradation by sophorolipid were 100% for MB and 86.834% for CR, suggesting the high emulsifying activity of biosurfactant (Ghribi et al, 2012) and demonstrating its enhancement of hydrocarbon biodegradation (Mnif et al, 2014). Antibacterial and anti-biofilm activity of biosurfactant Bacterial biofilms are a critical problem, especially for pathogens that exhibit strong drug resistance (El-Shounya et al, 2019;Mohamed et al, 2020a). Here, the antibacterial and antibiofilm effects of biosurfactant produced by Candida tropicalis were investigated on four MDR Klebsiella pneumoniae biofilm-producing pathogenic strains.…”
Section: Degradation Of Different Dyes Determined Using Ftir and Hplcmentioning
confidence: 99%